WebSpec: a visual language for specifying interaction and navigation requirements in web applications - Robles Luna, Esteban (2011)
Web application development is a complex and time-consuming process that involves different stakeholders (ranging from customers to developers); these applications have some unique characteristics like navigational access to information, sophisticated interaction features, etc. However, there have been few proposals to represent those requirements that are specific to Web applications. Consequently, validation of requirements (e.g., in acceptance tests) is usually informal and as a result troublesome. To overcome these problems, we present WebSpec, a domain-specific language for specifying the most relevant and characteristic requirements of Web applications: those involving interaction and navigation. We describe WebSpec diagrams, discussing their abstraction and expressive power. With a simple though realistic example, we show how we have used WebSpec in the context of an agile Web development approach discussing several issues such as automatic test generation, management of changes in requirements, and improving the understanding of the diagrams through application simulation.